High platelet reactivity – the challenge of prolonged anticoagulation therapy after ACSI - Brouwer, Marc A.; Focks, Jeroen Jaspers; Verheugt, Freek W. A. (Thrombosis and Haemostasis, 2013)
Despite dual antiplatelet therapy (DAPT), one-year event rates after acute coronary syndrome (ACS) vary from 9–12%. The development of novel oral anticoagulants (NOAC) without a need for monitoring has initiated renewed interest for prolonged adjunctive anticoagulation. Importantly, the cornerstone of treatment after ACS consists of long-term DAPT. In that context, the NOACs have only been tested as adjunctive therapy. Of all new agents, only rivaroxaban –in a substantially lower dose than used for atrial fibrillation– has been demonstrated to improve outcome, albeit at the cost of bleeding. In selected cases, adjunctive therapy with dose-adjusted vitamin-K antagonists (international normalized ratio [INR] 2.0–3.0) can be considered as well. These two strategies of prolonged anticoagulation can be considered in case of ‘high platelet reactivity’, i.e. in patients at high risk of recurrent thrombotic events despite DAPT. Both during admission and after discharge for ACS, the use of NOACs in doses indicated for atrial fibrillation is strictly contra-indicated in patients on DAPT. In case of post-discharge anticoagulation therapy for atrial fibrillation, patients should preferably receive vitamin-K antagonists (INR 2.0–3.0), with discontinuation of one antiplatelet agent as soon as clinically justifiable. Importantly, the impact of prolonged anticoagulation (low-dose rivaroxaban, vitamin-K antagonists) as adjunctive to DAPT after ACS has not been addressed with the most potent antiplatelet agents (prasugrel, ticagrelor) and merits further study. Despite the potential indication of prolonged oral anticoagulation as adjunctive treatment, it remains to be established whether anticoagulation therapy could also be an alternative for either aspirin or thienopyridine treatment in selected ACS patients on DAPT.
Keywords: Clinical trials; oral anticoagulants; coronary syndrome; direct antithrombin agents; coagulation inhibitors; heparins